Analysis of the Determinants of Provincial Income Inequality in Indonesia - Taufiq Akbar, A.; Ratih Y.T., Arivina; Murwiati, Asih; Emalia, Zulfa (Lafadz Jaya Publisher, 2024)
This research aims to analyze the influence of economic growth, the contribution of the agricultural sector, the contribution of the industrial sector, and the level of open unemployment on income inequality in all provinces in Indonesia. The method and analytical tools used in this research are panel data regression. The dependent variable used is the Gini index for all provinces in Indonesia and the independent variables include economic growth, agricultural sector contribution, industrial sector contribution and open unemployment rate. The best model obtained is the Fixed Effect Model. The research results show that economic growth, the contribution of the agricultural sector has a positive and significant effect on income inequality in all provinces in Indonesia, while the contribution of the industrial sector and the open unemployment rate do not have a significant effect on income inequality in all provinces in Indonesia.